A Randomized Double Blinded Placebo-Controlled Clinical Trial of a Probiotic or Metronidazole for Acute Canine Diarrhea - Shmalberg, Justin; Montalbano, Christina; Morelli, Giada; Buckley, Gareth J. (Frontiers in Veterinary Science, 2019)
Acute diarrhea is a common, often self-limiting, cause of presentation for veterinary care, yet there is a paucity of data on frequently-prescribed treatments. The purpose of this randomized, double blinded placebo-controlled clinical trial was to compare two anecdotally-recommended treatments: a probiotic combination and metronidazole. Sixty dogs without concurrent comorbidities were randomized into three treatment groups. The time to resolution of diarrheal signs was evaluated using owner surveys and fecal scoring charts. Dogs presenting with acute diarrhea achieved acceptable fecal consistency after 3.5±2.2 days when receiving probiotic, 4.6±2.4 days with oral metronidazole, and 4.8±2.9 days with placebo; statistically significant differences were not identified between treatment groups (p=0.17). These findings failed to provide evidence for the common use of metronidazole in this cohort of dogs with acute canine diarrhea, and a larger study population would be required to identify a statistically significant effect of probiotics.